Using a Hybrid Securities Test to Tackle the Problem of Pyramid Fraud - C. Matthews (Russian Journal of Economics and Law, 2021)
Objective: to research the hybrid securities test as a regulatory tool against pyramid schemes.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors, which predetermined the following research methods: formal-logical, comparative-legal, and sociological.Results: the work examines federal securities law as a tool to deter and regulate illegal pyramid schemes. Pyramid schemes are among the most prevalent forms of consumer fraud in the United States and they victimize thousands of individuals every year. The rise of the internet and social media has made it even easier for pyramid promoters to target potential recruits, often those who are already particularly vulnerable to consumer fraud. The federal securities laws have proven to be robust regulatory tools against pyramid schemes. However, the test used by federal courts to determine whether a scheme meets the definition of a security has produced uncertainty and inconsistency in the law. This work proposes that when pyramid schemes are alleged, federal courts should apply a hybrid securities test that incorporates aspects of risk capital analysis. In so doing, courts will be better equipped to focus on the economic reality of pyramid schemes and to draw a more principled line between illegal pyramid fraud and legitimate enterprises. Scientific novelty: the work proves that the problem of pyramid fraud is only growing. Despite the investment of significant governmental resources, undeterred fraudsters continue to form new pyramid schemes with growing regularity. The federal securities laws were enacted to protect the public from precisely these kinds of unsubstantiated, misleading, and fraudulent investment opportunities. However, courts inconsistently applying the Howey test continue to draw unprincipled lines and exclude pyramid schemes from the ambit of the federal securities laws based on the red herring of investor efforts. This work argues not that the federal courts should ignore the role played by distributors in pyramid schemes but rather that they should focus attention on the degree of control that investors may exercise as a function of that participation.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activities when considering issues related to using the hybrid securities test as a regulatory tool against pyramid schemes.